World trends in fertilizer use and projections to 2020 - Bumb, Balu L.; Baanante, Carlos A. (International Food Policy Research Institute, 1996)
Fertilizers have played an important role in increased crop production, especially in cereal yields, and will continue to be a cornerstone of the science-based agriculture required to feed the expanding world population. Fertilizers replenish the nutrients removed from soils by harvested crops, encourage adoption of high-yielding varieties, and increase biomass in the nutrient-poor soils of the tropics. Bumb and Baanante trace fertilizer use until the 1990s as well as production and price trends. Finally they propose projected trends in use, requirements, and production. The authors conclude that, overall, a conducive and stable policy environment, including macroeconomic stability, price incentives, credit availability, efficient organizational arrangements, research and extension support, regulatory frameworks, and environmental monitoring, will be essential to promote environmentally friendly growth in fertilizer use and supply to 2020.